Eco-friendly bupropion detection sensor with co-formulated dextromethorphan in AUVELITY tablet and spiked plasma - Shrouk E. Algmaal; Amr M. Mahmoud; Shereen A. Boltia; Yasser S. El-Saharty; Nermine S. Ghoniem (Scientific Reports)
Abstract Molecularly Imprinted Polymers (MIPs) are synthetic materials designed to selectively recognize and bind to specific target molecules. The process of determining Bupropion (BUP) using MIPs involves preparing the MIP, extracting the target molecule, and conducting subsequent analysis. A bio-inspired MIP-based electrochemical sensor was developed to detect BUP, utilizing the specific binding of MIPs to Bupropion molecules, enabling precise and sensitive detection. The combination of molecular imprinting and electrochemistry in this approach allows for the development of a highly reliable and effective sensor specifically designed for BUP detection. In this method, copolymerization conditions were carefully optimized to ensure selectivity and sensitivity in detecting BUP. Different monomers, including o-phenylenediamine, 4-aminophenol, L-dopa, and 1,4-phenylenediamine, were explored, with the best interaction observed for L-dopa and 1,4-phenylenediamine. Consequently, their copolymer was implemented to create selective MIPs through a straightforward electropolymerization process on a disposable pencil graphite electrode (PGE) substrate for BUP detection. The functionality of the copolymer of L-dopa and 1,4-phenylenediamine as an electroactive copolymer in preparing electro-polymerized MIP films was investigated for the first time. This was demonstrated by constructing a novel electrochemical sensor for the selective recognition of BUP in different matrices. The interactions between L-dopa and 1,4-phenylenediamine, used as functional monomers, and the template were studied experimentally using UV spectroscopy. BUP was used as the template, and the copolymer was electrografted onto PGE. The constructed sensor was characterized using cyclic voltammetry (CV), and BUP binding to the MIP cavities was measured indirectly with differential pulse voltammetry (DPV) using a ferrocyanide/ferricyanide redox probe. A linear and repeatable response was displayed by the sensor across a range of 1.0 × 10⁻13 M to 1.0 × 10⁻11 M of BUP, with a limit of detection of 3.18 × 10⁻14 M. The sensor demonstrated robust selectivity for BUP over interfering drugs, such as dextromethorphan, in pharmaceutical dosage forms and spiked human plasma. The environmental impact of the proposed approach was evaluated using green analytical chemistry principles, including the Green Analytical Procedure Index (GAPI) and the Analytical GREEnness (AGREE) metric.